Commensal Bacteria-Specific CD4+ T Cell Responses in Health and Disease - Sorini, Chiara; Cardoso, Rebeca F.; Gagliani, Nicola; Villablanca, Eduardo J. (Frontiers in Immunology, 2018)
Over the course of evolution, mammalian body surfaces have adapted their complex immune system to allow a harmless coexistence with the commensal microbiota. The adaptive immune response, in particular CD4+ T cell-mediated, is crucial to maintain intestinal immune homeostasis by discriminating between harmless (e.g. dietary compounds and intestinal microbes) and harmful stimuli (e.g. pathogens). To tolerate food molecules and microbial components, CD4+ T cells establish a finely tuned crosstalk with the environment whereas breakdown of these mechanisms might lead to chronic disease associated with mucosal barriers and beyond. How commensal-specific immune responses are regulated and how these molecular and cellular mechanisms can be manipulated to treat chronic disorders is yet poorly understood. In this review, we discuss current knowledge of the regulation of commensal bacteria-specific CD4+ T cells. We place particular focus on the key role of commensal-specific CD4+ T cells in maintaining tolerance while efficiently eradicating local and systemic infections, with a focus on factors that trigger their aberrant activation.